Effects of an offloaded running versus active recovery on performance after an ultramarathon-race - Burger, Amy (2019)
Background: The endurance running training process, which includes competition and recovery, requires managing a complex interaction of positive training adaptations and negative effects such as exercise-induced muscle damage (EIMD). Various active recovery interventions have been explored to speed up recovery from events such as ultra-marathon runs. This includes offloaded recovery strategies such as deep water running (DWR). More recently, the use of an anti-gravity treadmill for offloaded recovery after a cardio-vascular event such as an ultra-marathon race has been proposed. There is however, limited research to support this, as well as how to appropriately test this as a recovery strategy. Aim To investigate the effects of an offloaded running recovery intervention compared to a standard active recovery strategy on running performance and markers of recovery after an ultra-marathon race. Specific Objectives: The specific objectives were to 1) compare differences in a 5 km time trial performance between an experimental group (who received an offloaded recovery intervention on an anti-gravity treadmill) and a control group (who received a standard active recovery protocol) 14 days before and ten days after an ultra-marathon race; 2) To compare secondary outcome measures of heart rate and rate of perceived exertion during these 5 km time trial, 3) To compare differences in self-reported muscle and, 4) daily activity levels, between the two groups before the race; and over a seven-day period after the ultra-marathon race, 5) To compare heart rate, rating of perceived exertion, muscle pain and running speed of the experimental group runners during 30-minute offloaded recovery runs on an anti-gravity treadmill. Methods: Eighteen participants ran the Comrades ultra-marathon race to induced muscle damage. The experimental group consisted of nine male runners who performed an offloaded recovey protocol of three to four recovery runs, using an anti-gravity treadmill, in the week following the ultra-marathon. The control group consisted of nine male runners who perfromed a standard active recovery protocol in the week following the ultra-marathon. A 5 km time trial run was performed 14 days before, and ten days after the ultra-marathon. The participant’s rating of perceived exertion and heart rate and split speeds were measured during the time trial runs. Daily measurements of muscle pain (using a visual analogue scale that assessed muscle pain in the hamstrings, quadriceps and calf muscles) and daily activity levels (using pedometers) were recorded one day before and for seven days after the ultra-marathon. Results Groups were similar in demographics, racing experience and ultra-marathon performances. There were no significant differences in running speed during the 5-km time trial performance between groups, or pre-post the ultra-marathon race; however, there was a significant difference in the measurement over time (p < 0.00001). The study showed a significant interaction between groups over time pre-post the ultra-marathon race for heart rate (p = 0.008) and rating of perceived exertion (p = 0.008) during the 5-km time trial. There was a significant increase in all measures of pain, for all three muscle groups over-time (p < 0.00001) for both groups. Certain pain ratings were significantly lower in the experimental group on days three, four and five after the ultra-marathon. There was an observation of almost no pain during the 30-minute recovery runs on the anti-gravity treadmill performed by the experimental group. Discussion and Conclusion: The findings of this study suggest that there may be benefits in using the anti-gravity treadmill as a recovery tool that a) provided temporary relief in muscle pain during a recovery run and; b) may alleviate muscle pain once implemented in the days following an ultra-marathon race. Some improvements in heart rate and RPE during a 5-km time trial, were observed, supporting the potential effectiveness of an offloaded recovery in limiting some of the deleterious effects of EIMD after an ultra-marathon race. However, the benefits of using the anti-gravity treadmill, according to this study, are very limited. It is hoped that this study could provide bases for further investigation into antigravity treadmill running, as well as how to more accurately manipulate different percentages of body weight support, for recovery and training purposes.